Utrzymanie dróg w okresie zimowym – problematyka prawna zakresu obowiązków i odpowiedzialności zarządcy drogi publicznej - Bujny, Jędrzej; Kudra, Anna (Wydawnictwo Naukowe UAM, 2014)
This article is an attempt to reconstruct legal regulations, including the existing solutions in the doctrine and judicial decisions, regarding the scope of duties of public road managers when it comes to road maintenance in winter time and liability thereof. The relevant provisions regulating this matter are highly laconic and are practically reduced to a general indication that it is the public road manager’s duty to clear roads of snow and fi ght slippery winter surfaces. There is no mention though, of the degree to which these measures must be taken, or the legal instruments available for organising work on roads. Interpretation of the existing provisions suggests that maintenance of roads in winter is a very complex process and covers a number of activities undertaken to reduce traffi c disturbances. Public roads managers enjoy a certain freedom as regards organisation of the work and the type of work to be conducted on roads. This freedom manifests itself, among other things, by different standards adopted for winter road maintenance, depending on the road category and its importance in the overall road network. The analysis of the existing solutions and judgments allows to conclude that the liability of a public road manager for losses incurred by road users in winter time is not strict (absolute). Thus, in the assessment of a road manager work, a reference must be made to the principle of due care expected from a professional, having regard however, to the objective premises and circumstances. Public road managers’ liability is also correlated with the liability of road users for unsafe driving under increased caution conditions. In light of the conducted analysis it may be stated that ensuring full passability of roads in winter time is not an absolute duty of a public road manager. Public road managers are merely obliged to maintain a road in a condition guaranteeing safety in given weather conditions, having account to the fi nancial and human resources they have at their disposal.
The maintenance of roads in winter – the scope of duties and liabilities of a public road manager
Keywords: public roads; duties of public roads users; road manager; winter; road safety